Understanding jet scaling and jet vetos in Higgs searches - Gerwick, Erik; Plehn, Tilman; Schumann, Steffen (Physical review letters, 2012)
Jet counting and jet vetos are crucial analysis tools for many LHC searches. We can understand their properties from the distribution of the exclusive number of jets. LHC processes tend to show either a distinct staircase scaling or a Poisson scaling, depending on kinematic cuts. We illustrate our approach in a detailed study of jets in weak boson fusion Higgs production.